Development and Validation of a Bilingual Stroke Preparedness Assessment Instrument - Skolarus, Lesli E. (Stroke, 2017)
BACKGROUND AND PURPOSE: Stroke preparedness interventions are limited by the lack of psychometrically sound intermediate endpoints. We sought to develop and assess the reliability and validity of the video-Stroke Action Test, video-STAT, an English and Spanish video-based test to assess people’s ability to recognize and react to stroke signs. METHODS: Video-STAT development and testing was divided into four phases: 1) video development and community-generated response options; 2) pilot testing in community health centers; 3) administration in a national sample, bilingual sample and neurologist sample; and 4) administration before and after a stroke preparedness intervention. RESULTS: The final version of the video-STAT included 8 videos: 4 acute stroke/emergency, 2 prior stroke/non-emergency, 1 non-stroke/emergency, 1 non-stroke/non-emergency. Acute stroke recognition and action response were queried after each vignette. Video-STAT scoring was based on the acute stroke vignettes only (score range 0–12 best). The national sample consisted of 598 participants, 438 who took the video-STAT in English and 160 who took the video-STAT in Spanish. There was adequate internal consistency (Cronbach’s alpha=0.72). The average video-STAT score was 5.6 (sd=3.6) while the average neurologist score was 11.4 (sd=1.3). There was no difference in video-STAT scores between the 116 bilingual video-STAT participants who took the video-STAT in English or Spanish. Compared to baseline scores, the video-STAT scores increased following a stroke preparedness intervention (6.2 vs. 8.9, p<0.01) among a sample of 101 African American adults and youth. CONCLUSION: The video-STAT yields reliable scores that appear to be valid measures of stroke preparedness.